Removal of HCl from a gas phase by MgO under atmospheric conditions - Michiko Kitagawa; Hiromi Matsuhashi; Masanori Kidera; Kazuya Takahashi; Takahiro Kondo (Science and Technology of Advanced Materials)
Ensuring the safety of researchers by protecting them from exposure to toxic gases in laboratories is of paramount importance. This study investigated the effectiveness of using high-surface-area MgO to remove HCl under atmospheric conditions. Two types of MgO were synthesized through the thermal decomposition 1-1-1, Tennodai, Tsukuba, of Mg(OH)2 and MgC2O4·2 H2O. HCl diluted with air passed through both MgO samples, and the amounts of HCl removed and morphological changes in the samples were compared. No significant differences in surface area or crystallinity were observed with the decomposition temperatures. X-ray diffraction analysis showed that the sample prepared from MgC2O4·2 H2O reacted with HCl immediately upon introducing HCl gas. In contrast, the sample obtained from Mg(OH)2 exhibited only MgO peaks, even 30 min after the introduction of HCl gas. Microscopic analysis revealed that the samples derived from Mg(OH)2 showed no significant changes in shape after the reaction, whereas the MgO prepared from MgC2O4·2 H2O exhibited substantial changes in overall shape. No correlation was observed between the surface area and the amount of HCl removed. When MgO is prepared from MgC2O4·2 H2O, the reaction occurs in the bulk material, whereas when MgO is prepared from Mg(OH)2, the reaction hardly progresses after HCl adsorbs onto the MgO surface. The order of magnitude of HCl removal was consistent with the base catalytic activity of the decomposition of diacetone alcohol to acetone. These results suggest that, compared with MgO obtained from Mg(OH)2, MgO derived from MgC2O4·2 H2O generates more active sites, resulting in the reaction with HCl from surface to progress into bulk.